Baicalein inhibits the progression of thyroid cancer by suppressing the TPL2/MEK2/ERK2 pathway - Wu, Nan; Wu, Yang; Zhang, Qian; Naeem, Muhammad; Jing, Ren; Luo, Yuan-bin; Yi, Shijian (Frontiers in Endocrinology, 2026)
IntroductionPapillary thyroid cancer (PTC) is the most common type of endocrine malignancy caused by genetic mutations, hormonal imbalances, and environmental factors. However, recurrent infections, and metastasis in PTC patients remain challenged due to complexity of traditional methods. Baicalein (BA) is a kind of natural flavonoid that exhibits the anti-cancer, anti-inflammatory, anti-tumor, and anti-viral activities. The molecular mechanism of baicalein in pathogenesis of PTC remains unclear. This study was designed to explore the inhibitory effects of BA against PTC by mediating the Golgi apparatus reprogramming via PLAU and suppressing the TPL2/MEK2/ERK2 pathway.MethodsTranscriptomic analysis was performed to explore the gene expression profiles. Molecular docking was employed to identify the potential targets to elucidate the molecular mechanism of action of BA.ResultsPLAU, an up-regulated DEG, is implicated in tumor development, lymph node metastasis, and infiltration levels of neutrophils and dendritic cells in thyroid cancer patients. Molecular docking analysis revealed that serum levels of uPA protein encoded by PLAU and Plau mRNA were elevated in PTC patients with metastasis and BRAF mutation. BA treatment upregulates PLAU gene expression, but this increased PLAU protein subsequently interacts with and inhibited by BA, leading to downstream pathway suppression.ConclusionIt was concluded it could be served as a promising therapeutic strategy for the treatment of PTC.